From financial to real economic crisis: Evidence from individual firm-bank relationships in Germany - Nadja Dwenger; Frank M. Fossen; Martin Simmler (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
What began as a financial crisis in the United States in 2007-2008 quickly evolved into a massive crisis of the global real economy. We investigate the importance of the bank lending and firm borrowing channel in the international transmission of bank distress to the real economy-in particular, to real investment and labor employment by nonfinancial firms. We analyze whether and to what extent firms are able to compensate for the shortage in loan supply by switching banks and by using other types of financing. The analysis is based on a unique matched data set for Germany that contains firm-level financial statements for the 2004-2010 period together with the financial statements of each firm's relationship bank(s). We use instrumental variable estimations in first differences to eliminate firm- and bankspecific effects. The first stage results show that banks that suffered losses due to proprietary trading activities at the onset of the financial crisis reduced their lending more strongly than non-affected banks. In the second stage, we find that firms whose relationship banks reduce credit supply downsize their real investment and labor employment significantly. This effect islarger for firms that are unable to provide much collateral. We document that firms partially offset reduced credit supply by establishing new bank relationships, using internal funds, and issuing new equity.
Keywords: D22; D92; E44; G01; G20; G31; H25; H32; 330; financial crisis; contagion; credit rationing; relationship lending; investment